Exploring programmatic issues which affect continuing legal education practice in Kansas - Fisher, Holly B. (Kansas State University, 2017)
As individuals, we rely on the expertise of professionals to help us navigate the complex problems of modern life in areas such as medicine, accounting, social work, teaching, and the law. Although each profession has its own unique knowledge base, lexicon, and culture, they all share the need to keep members’ knowledge and skills current through continuing professional education. Driven by concerns like frequent law change, increasingly complex clients, and eroding public opinion, 46 states have instituted mandatory continuing legal education (MCLE) requirements for attorneys. The Kansas Continuing Legal Education (CLE) Commission administers MCLE in the state of Kansas by monitoring attorney compliance and accrediting CLE programs. In this study, the researcher used a mixed-methods approach to evaluate two existing data sets--survey outputs and focus groups transcripts--that were captured during the Kansas CLE Commission’s Education Initiative. The 260 CLE providers completing the survey and 22 focus group members varied demographically by structure (for-profit, nonprofit) and size (number of employees or course offerings). Using quantitative statistical tools and qualitative grounded theory methods, the researcher identified the current program planning and design, delivery, and evaluation practices of CLE providers in Kansas and evaluated these practices against best practices for any learning effort, as established by CPE research and theory. Study findings indicated that most Kansas providers plan, deliver, and evaluate CLE programs using more traditional, didactic, update-oriented approaches. Most participants reported CLE curricula that were focused on keeping attorneys up-to-date, delivering classes in traditional formats using speaker presentations, and evaluating programs with Level 1 reaction methods. Only some evidence existed of providers determining attorney needs using methods such as competency models or performance evaluations, refining course delivery according to learning styles, or evaluating programs at higher levels. Still, evidence was found of providers using creative ways to incorporate some best practices into their programs, such as partnering with the other stakeholders in the Kansas MCLE space (attendees, employers, and regulators) to plan and evaluate programs. Similarly, some providers are finding new ways to incorporate more interactive learning methods into their classrooms such as discussion groups, Q&A sessions, panels, mock trials, and networking. This research also provided important insights into the contextual realities and limitations that influence MCLE provider capabilities, priorities, or choices. Cultural norms of the legal profession such as a preference for traditional educational experiences, fierce opposition to any form of testing, and a focus on billable hours affect which best practices the providers are able to implement. Likewise, the diversity that exists across learning events, law practices, and providers in this space creates challenges to implementing new practices consistently across all programs. Finally, the fragmented, multistakeholder ownership of all Kansas MCLE processes means that providers alone are not able to implement fully the recommended best practices without the help of employer partners. This study added to the general body of knowledge concerning CLE programs with contemporary research, a new focus on providers as the source of data, and a context-specific assessment of current best practices application.
Keywords: Mandatory continuing legal education; Continuing professional education; Educational program design; Educational program delivery; Educational program evaluationContinuing legal education